2013
DOI: 10.2174/09298665113209990089
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Structure of PTP1B in Complex with a New PTP1B Inhibitor

Abstract: Protein tyrosine phosphatase 1B (PTP1B) is a prototype non receptor cytoplasmic PTPase enzyme that has been implicated in regulation of insulin and leptin signaling pathways. Studies on PTP1B knockout mice and PTP1B antisense treated mice suggested that inhibition of PTP1B would be an effective strategy for the treatment of type II diabetes and obesity. Here we report the X-ray structure of PTP1B in complex with compound IN1834-146C (PDB ID 4I8N). The crystals belong to P3121 space group with cell dimensions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…To sults [18]. This result showed that the docking technique and parameters used in the present study were similar in the PTP1B system.…”
Section: Molecular Dockingsupporting
confidence: 68%
See 1 more Smart Citation
“…To sults [18]. This result showed that the docking technique and parameters used in the present study were similar in the PTP1B system.…”
Section: Molecular Dockingsupporting
confidence: 68%
“…The X-ray crystal complex of PTP1B-IN1834146C (Named: Compound 19 in this study) was downloaded from the database of RCSB Protein Data Bank (PDB) (http://www.pdb.org/pdb/home/home.do), and the PDB code was 2VEU [18]. The structure was prepared in the following procedures: 1) removing the co-crystallized ligand of 19 and structural water molecules from the crystal structure, 2) adding hydrogen atoms to the protein by the Biopolymer module implemented in the SYBYL X1.3, and 3) assigning the Kollman-All atom charges to the protein atoms.…”
Section: Data Preparationmentioning
confidence: 99%
“…The docking result of silydianin was also compared with some of the reported inhibitors (PDB ID: 5T19, 2QBP, 1T49 and 4I8N) and it was observed to be interacting with the residues of the active site. Arg221 and Gln266 were observed to be common interacting residues in silydianin and the reported inhibitors [ 60 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…PTP1B is also as key player in cancer serving as both tumor promoter and tumor suppressor depending on the cellular context. (Shi et al, 2008;Barr, 2010;Feldhammer et al, 2013;Malla, Kumar, Kumar, 2013;Reddy et al, 2014).…”
Section: Effects Of Derivatives 2a-2o On Cdc25b and Ptp1b In Vitromentioning
confidence: 99%